Radio-frequency connectors. Two-pole screw (¾-20 UNEF) coupled connectors for use with shielded balanced cables having twin inner conductors with inner diameter of outer conductor 13, 56 mm (0, 534 in) (Type TWHN) Part 25, (15th March 1994) - British Standards Institution,
No abstract available